2011
DOI: 10.2147/vhrm.s15429
|View full text |Cite
|
Sign up to set email alerts
|

Vasodilatory effects of cinnamaldehyde and its mechanism of action in the rat aorta

Abstract: The vasodilatory effect of cinnamaldehyde was investigated for its mechanism of action using isolated rings of rat aorta. Cinnamaldehyde relaxed aortic rings precontracted with phenylephrine in a dose-dependent manner, was not affected by either the presence or removal of the endothelium. Pretreatment with NG-nitro-L-arginine methyl ester and 1H-[1,2,4]-oxadiazole-[4,3-a]-quinoxalin-1-one could not block vasodilation by cinnamaldehyde, indicating that nitric oxide signaling is not involved. Potassium channel b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 16 publications
1
20
0
Order By: Relevance
“…When carried in micelles, cinnamaldehyde was also able to induce endothelium-dependent vascular relaxation by NO- and H 2 O 2 -dependent means. This was also demonstrated by Xue et al [ 43 ], who showed that this relaxant effect of cinnamaldehyde was likely mediated by changes in calcium influx or in its release from intracellular stores. Additionally, Alvarez-Collazo et al [ 44 ] studied the mechanism of action of this compound and showed that CA promoted relaxation in vascular smooth muscle cells (VSMC) and ventricular cardiac myocytes (VCM), at least in part by inhibition of the L-Type Ca 2+ channel.…”
Section: Resultssupporting
confidence: 65%
“…When carried in micelles, cinnamaldehyde was also able to induce endothelium-dependent vascular relaxation by NO- and H 2 O 2 -dependent means. This was also demonstrated by Xue et al [ 43 ], who showed that this relaxant effect of cinnamaldehyde was likely mediated by changes in calcium influx or in its release from intracellular stores. Additionally, Alvarez-Collazo et al [ 44 ] studied the mechanism of action of this compound and showed that CA promoted relaxation in vascular smooth muscle cells (VSMC) and ventricular cardiac myocytes (VCM), at least in part by inhibition of the L-Type Ca 2+ channel.…”
Section: Resultssupporting
confidence: 65%
“…Cinnamaldehyde (CA) is a commonly used TRPA1 agonist, selected due to its relative selectivity and potency (Bandell et al 2004 ). It has been shown to cause vasorelaxation and vasodilation in several studies (VanderEnde and Morrow 2001 ; Namer et al 2005 ; Yanaga et al 2006 ; Pozsgai et al 2010 ; Xue et al 2011 ). Our group has also recently demonstrated CA induced ex vivo vasorelaxation and in vivo vasodilation responses to be significantly reduced in TRPA1 knockout (KO) mice (Pozsgai et al 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…In line with the role for TRPA1 in inflammation, several groups demonstrate TRPA1 agonists to cause vasorelaxation or vasodilation, occurring in a range of species and vascular beds (Bodkin and Brain 2010 ). TRPA1-induced vasorelaxation is commonly identified to be neuropeptide mediated (Louis et al 1989 ; Morris et al 1999 ; Hikiji et al 2000 ; Grant et al 2005 ; Namer et al 2005 ; Graepel et al 2011 ; Kunkler et al 2011 ), while other studies propose direct changes in calcium handling (Yanaga et al 2006 ; Earley et al 2009 ; Xue et al 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…In 2011, Xue et al indicated that cinnamaldehyde increased rat vascular smooth muscle in an endotheliumindependent method. The capability of cinnamaldehyde in vasodilatory performance might be due to inhibition of both Ca 2+ invasion and Ca 2+ discharge (39). Likewise, cinnamaldehyde prevents the development of hypertension in types I and II diabetes by reducing vascular contractility, as well as its insulinotropic effect in insulin fault (40).…”
Section: Methodsmentioning
confidence: 99%